Soft Condensed Matter in Pharmaceutical Design - Paradossi, Gaio; Cavalieri, Francesca; Chiessi, Ester (Current Pharmaceutical Design, 2006)
In recent years pharmaceutical design has been facing the needs expressed by new therapeutic methodologies such as gene therapy, targeted delivery and closely related diagnostic fields as contrast enhancing agents for ultrasonic investigations. In this context pharmaceutical research has diversified the efforts toward a more integrated approach where the efficacy of an active molecule is enhanced and assisted by the surrounding carrier. Usually this drug platform is a hydrogel matrix, a multicomponent system constituted by an aqueous solution and a polymeric moiety imparting different functions to the matrix, as responsiveness to external stimuli, affinity to receptors, controlled drug release. Such devices represent one of the leading topics of the soft condensed matter recent research, a domain where physics, chemistry and bioengineering cross each other with the aim to achieve an integrated description of these materials. In this respect modern drug design will make use more and more of concepts proper of soft condensed polymer and colloidal sciences. In this review we will describe the state-of-art in the field of the matrices used in innovative drug formulations with a particular emphasis on the implications to pharmaceutical design along with the experimental and theoretical investigation tools worked out in the last decade.
Keywords: drug delivery